Análises de ações manipulativas em crianças da primeira infância praticantes de natação - Geamonond, Leonardo (2017)
The aim of this study was to evaluate the manipulative function of children from early childhood swimmers. The study included ten children swimmers of both gender in Uberlândia-MG. The selection was made randomly. The evaluation protocol of the aquatic motor development "Observation sheet of psychomotor aquatic Evolution" (by its acronym in Portuguese HOEPA) was used. This study found that 30.5% of students manipulated objects of different sizes and grabbed the edge of the pool, 20.5% of them found no problem in moving objects with their hands. The results of this research lead us to conclude that the aquatic psychomotor development in ball handling is deficient, so we must intervene early in the changes and stimulate normal development.
O objetivo deste estudo foi avaliar a funçao manipulativa de crianças da primeira infância praticantes de nataçao. Participaram deste estudo dez crianças de ambos os sexos praticantes de nataçao na cidade de Uberlândia-MG a seleçao foi realizada de forma aleatória. Foi utilizado o protocolo de avaliaçao do desenvolvimento motor aquático (HOEPA) "Hoja de Observación para la Evolución de la Psicomotricidad Acuática". O presente estudo identificou que 30,5% dos alunos as vezes manipulavam os objetos de diferentes tamanhos e levavam a borda da piscina, 20,5% nao encontraram problemas em deslocar-se com objetos nas maos. Os resultados obtidos nesta pesquisa nos leva a concluir que o desenvolvimento psicomotor aquático na esfera manipulaçao se encontra deficitário, devemos intervir precocemente nas alteraçoes bem como estimular o desenvolvimento normal
Keywords: Manipulative function; Motor Control; Swimming; Children; Funçao Manipulativa^lpt; Controle Motor; Nataçao; Crianças